Affairs of honor national politics in the New Republic - Freeman, Joanne B., 1962-; ebrary, Inc. (New Haven : Yale University Press, 2001)
"In this book, Joanne Freeman offers a major reassessment of political culture in the early years of the American republic. By exploring both the public actions and private papers of key figures like Thomas Jefferson, Aaron Burr, and Alexander Hamilton, as well as less famous politicians such as Senators William Maclay and William Plumer, Freeman reveals an alien and profoundly unstable political world grounded on the code of honor. In the absence of a party system and with few examples to guide America's great experiment in republican governance, national politicians monitored their conduct and attacked their rivals according to the ethic of honor."
Includes bibliographical references (p. 347-364) and index.
Electronic reproduction.
Keywords: Political culture -- United States -- History -- 18th century; Politics and culture -- United States -- History -- 18th century; Elite (Social sciences) -- United States -- Political activity -- History -- 18th century; Honor -- Political aspects -- United States -- History -- 18th century; United States -- Politics and government -- 1789-1815.; United States -- Social conditions -- To 1865.; Electronic books